Reduction of pier scour using bed suction and jet injection - Soltani-Gerdefaramarzi, Somayeh (2015)
The influence of a combined system of jet injection through the pier and bed suction on the reduction of local scour around a circular pier was investigated in a laboratory flume. Experiments were conducted for two water depths (10·5 and 28 cm) under 1-jet and 3-jet injection and different angles between the jets, with bed suction rate Q s /Q 0 = 2%, in turbulent flow and clear-water scouring conditions. The results show that the bed suction modifies the effect of jet scouring and reduces the local scour and sediment transport at the pier (36% for scour depth, 25 and 42% for the area and volume of scour hole). The maximum reduction of the scour depth was about 50% (about 20, 39 and 39% for the area, volume and the upstream slope of the scour hole respectively) in the best configurations for a combined countermeasure.